2014
DOI: 10.1038/bjc.2014.137
|View full text |Cite
|
Sign up to set email alerts
|

A phase I pharmacokinetic study of the vascular disrupting agent ombrabulin (AVE8062) and docetaxel in advanced solid tumours

Abstract: Background:The vascular disrupting agent ombrabulin shows synergy with docetaxel in vivo. Recommended phase II doses were determined in a dose escalation study in advanced solid tumours.Methods:Ombrabulin (30-min infusion, day 1) followed by docetaxel (1-h infusion, day 2) every 3 weeks was explored. Ombrabulin was escalated from 11.5 to 42 mg m−2 with 75 mg m−2 docetaxel, then from 30 to 35 mg m−2 with 100 mg m−2 docetaxel. Recommended phase II dose cohorts were expanded.Results:Fifty-eight patients were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 22 publications
0
17
0
1
Order By: Relevance
“…VDAs have been extensively studied in combination therapy of cancer treatment. [31][32][33][34] In particular, Sengupta et al [ 35 ] reported a nanoscale codelivery system of combretastatin A4 (CA4) and doxorubicin for tumor therapy. The system enabled focal sequential release of CA4 and doxorubicin within a solid tumor, and resulted in improved therapeutic index with reduced toxicity.…”
Section: Coadministration Of Vascular Disrupting Agents and Nanomedicmentioning
confidence: 99%
“…VDAs have been extensively studied in combination therapy of cancer treatment. [31][32][33][34] In particular, Sengupta et al [ 35 ] reported a nanoscale codelivery system of combretastatin A4 (CA4) and doxorubicin for tumor therapy. The system enabled focal sequential release of CA4 and doxorubicin within a solid tumor, and resulted in improved therapeutic index with reduced toxicity.…”
Section: Coadministration Of Vascular Disrupting Agents and Nanomedicmentioning
confidence: 99%
“…In this trial, ombrabulin was well tolerated with limited cardiovascular side effects. Furthermore, in three additional phase I trials, ombrabulin has recently shown manageable and comparable overlapping toxicities to those observed in previous safety/pharmacokinetic studies . Von Pawel et al.…”
Section: Targeting the Tumor Vasculature By Natural Compounds: Perspementioning
confidence: 80%
“…In this trial, ombrabulin was well tolerated with limited cardiovascular side effects. Furthermore, in three additional phase I trials, ombrabulin has recently shown manageable and comparable overlapping toxicities to those observed in previous safety/pharmacokinetic studies [122][123][124]. Von Pawel et al [125] randomized 176 patients with metastatic NSCLC in a phase II trial (DISRUPT) to receive ombrabulin (n = 88, 35 mg/m 2 ) or placebo (n = 88) followed by taxane-platinum doublet q3 wk as first-line therapy.…”
Section: Ombrabulin (Ave8062)mentioning
confidence: 97%
“…Vascular‐disrupting agents (VDAs) are a relatively new class of drugs that act on the established tumor vasculature, causing hypoxia and necrosis of the tumor mass . Tubulin colchicine binding site inhibitor VDAs have been most extensively tested in clinical trials . Common toxicities of these agents include nausea, diarrhea, tumor pain, and hypertension .…”
Section: Introductionmentioning
confidence: 99%
“…Tubulin colchicine binding site inhibitor VDAs have been most extensively tested in clinical trials . Common toxicities of these agents include nausea, diarrhea, tumor pain, and hypertension . CKD‐516 (NOV120401), developed by Chong Kun Dang (Seoul, Korea), is a VDA prodrug that is rapidly converted into the active moiety, S‐516 .…”
Section: Introductionmentioning
confidence: 99%